Care and choice in dealing with the invasive cane toad in Western Australia - Nyquist, Jon Rasmus (The Australian journal of anthropology, 2014)
This article examines the meeting between the community group Kimberley Toad Busters (KTB) and established science and government in terms of an intersection of two logics of engagement. A logic of choice and a logic of care meet in the first example where I look at the conflicts and tensions arising in a public forum on control of cane toads in the Kimberley region of Western Australia. The second part of the article presents two examples of KTB's own practices to demonstrate that the tension between the two logics also figures within these practices. Nature is enacted both similarly and differently in these events through the tension between the logic of care and the logic of choice. In the first instance the logics figure as mutually exclusive and generative of an expanding gulf between lay and scientific knowledge, while in the second the two emerge in an unfinished productive tension.